Toriko. Part 02. Episodes 14-26 [videorecording (DVD)] - Shimabukuro, Mitsutoshi, 1975- (FUNimation Productions, Ltd., 2011)
The tummy-grumbling, lip-smacking, culinary adventure continues! The next step in Toriko's quest to create his Full Course Menu of Life involves a run-in with the ferocious Regal Mammoth! Beneath this behemoth's brutish exterior lies the legendary Jewel Meat, a magically magnificent morsel that makes mouths water all across the galaxy! Toriko is determined to make the beast his next carnivorous conquest, but he'll have to take the fight inside the mammoth if he hopes to sink his teeth into a humongous hunk of Jewel Meat! And that's not all! The Gourmet Hunter faces stiff competition in the form of a GT Robot. This seemingly indestructible mechanized menace is controlled by an unseen evil, and it wants the Jewel Meat all for itself! To save his friends and quench his heroic appetite, Toriko must level up his punching power and turn the bad guy into a bucket of bolts!